AIM2 and Psoriasis - Zhang, Yuxi; Xu, Xiaoqing; Cheng, Hui; Zhou, Fusheng (Frontiers in Immunology, 2023)
Psoriasis is a chronic inflammatory skin disease occurring worldwide, with multiple systemic complications, which seriously affect the quality of life and physical and mental health of patients. The pathogenesis of psoriasis is related to the environment, genetics, epigenetics, and dysregulation of immune cells such as T cells, dendritic cells (DCs), and nonimmune cells such as keratinocytes. Absent in melanoma 2 (AIM2), a susceptibility gene locus for psoriasis, has been strongly linked to the genetic and epigenetic aspects of psoriasis and increased in expression in psoriatic keratinocytes. AIM2 was found to be activated in an inflammasome-dependent way to release IL-1β and IL-18 to mediate inflammation, and to participate in immune regulation in psoriasis, or in an inflammasome-independent way by regulating the function of regulatory T(Treg) cells or programming cell death in keratinocytes as well as controlling the proliferative state of different cells. AIM2 may also play a role in the recurrence of psoriasis by trained immunity. In this review, we will elaborate on the characteristics of AIM2 and how AIM2 mediates the development of psoriasis.